Static and dynamic mechanical analysis of geometrically different kenaf/PLA green composite laminates. Issue 2 (31st October 2019) - Manral, Ankit; Bajpai, Pramendra K.
Abstract: The type of reinforcement used in polymer composite is one of the main governing parameters to ascertain the performance of a polymer composite. Green composites using fiber mat as reinforcement have shown promising results. In the present study, three different types of kenaf fiber mat (ie, bidirectional, unidirectional, and randomly oriented) have been incorporated with polylactic acid (PLA) for fabrication of green composite laminates through compression molding. Static mechanical characterization (tensile, flexural, and impact) of the developed composites has shown that type of fiber mat affects the mechanical performance of laminated composites markedly. Unidirectional fiber reinforced PLA composite has shown the highest tensile strength in comparison to bidirectional fiber reinforced PLA composite (BDFRPC) and randomly oriented fiber reinforced PLA composite (ROFRPC). BDFRPC has shown better flexural properties whereas ROFRPC achieved higher impact strength. Dynamic mechanical analysis of different kenaf/PLA laminates was performed to investigate the visco‐elastic nature with respect to temperature. Results show that ROFRPC has observed the best results under dynamic loading condition. The morphological study of the fractured surfaces during various testing was performed using scanning electron microscope to investigate mechanisms and reasons of failure of composites.